Diagnóstico para a desindustrialização do Brasil: doença holandesa ou custo Brasil? - Monteiro, Vitor Borges (2021)
Considering that the brazilian industry lost so early participation in the national aggregate in recent years, this study aimed to identify the main causes of this process of deindustrialization occurred in Brazil. There are two sources for such a process: the first is based on the so-called "Dutch Disease", which suggests that the appreciation of the real exchange rate due to the increase in exports of commodities would be able to generate a negative effect on the industry as a whole; and the second grounded in the idea of the "Brazil Cost", which suggests that the negative effect on the industry would be caused by the heavy weight of variables such as taxes and salaries. Principal component analysisBrazilian Journal of Development ISSN: 2525-8761 58707 Brazilian Journal of Development, Curitiba, v.7, n.6, p. 58706-58733 jun. 2021 (PCA) is used to measure an indicator that represents the Brazil Cost.Our proposal is to investigate the effect of these variables in the process of deindustrialization post “real plan” based on the vector autoregression (VAR) model. Our results maintain that both effects are harmful to the Brazilian industry, but the hypothesis of the Dutch disease further explains the decline in industry's share of GDP.